2013
DOI: 10.3923/pjbs.2013.2066.2069
|View full text |Cite
|
Sign up to set email alerts
|

Study on Analgesic and Anti-inflammatory Properties of Cordia myxa Fruit Hydro-alcoholic Extract

Abstract: Cordia myxa is a plant which is used in tropical regions of the world. Analgesic and anti-inflammatory effect of fruit of this medicinal plant was investigated in mice. Hydro-alcoholic extract of it was prepared by maceration method. Formalin test was conducted in six groups of mice (6 animals in each group) and acetic acid test in another six groups (6 mice). Groups one to six in each test were administered normal saline, oral indomethacin, intraperitoneal tramadol, 100 mg kg(-1) oral extract, 200 mg kg(-1) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Flowers of Acacia nilotica were used for the treatment of leucorrhea, the bulb of Allium sativum is used to control blood pressure, Latex from Bombax ceiba is used to cure menstrual problems, seeds of Cassia fistula are used for stomach disorders, powder from Citrullus colocynthis is used for constipation and to cure asthma, the fruit of Cordia myxa is used to cure ulcers of the stomach and joint pain and fruit yielding plants provide a rich source of food but also provide numerous vitamins. Previous studies also reported the use of these plants against cure of different diseases [ 33 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flowers of Acacia nilotica were used for the treatment of leucorrhea, the bulb of Allium sativum is used to control blood pressure, Latex from Bombax ceiba is used to cure menstrual problems, seeds of Cassia fistula are used for stomach disorders, powder from Citrullus colocynthis is used for constipation and to cure asthma, the fruit of Cordia myxa is used to cure ulcers of the stomach and joint pain and fruit yielding plants provide a rich source of food but also provide numerous vitamins. Previous studies also reported the use of these plants against cure of different diseases [ 33 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pathological (Orhan, 2015), and this is reflected in its positive effect on broiler birds added to their diets, the fruit of the Bumber, due to the clear improvement in most of the indicators of the study, especially since the birds are heat-stressed, which affects their breathing process. Oudhi (2007) and Al-Awadi and his group (2001) indicated that the therapeutic properties of the pamper fruit lie in its high content of biological active substances found in the fruit such as flavonoids, glycosides and fatty acids, especially oleic, linoleic and palmitic, as well as the high beta-sitosterol, these substances may be attributed The reason for the improvement in the birds during the experimental period compared to the control treatment under study, while Ranjbar et al (2013) confirmed in a study conducted to investigate whether there was a protective effect of the Bumber fruit in mice treated with tramadol and formalin. Glutathione SOD and total antioxidants, the reason for which the result of the aforementioned study is attributed to the antioxidant properties possessed by the elderberry fruit, as confirmed by Ficarra et al (1995) to the similarity of the analgesic effect between mefenamic acid and the elderberry fruit, while the moral improvement observed in the results of the study Current production characteristics such as average body weight, weight gain, feed consumption rate and feed conversion factor, always m It is associated with the observed improvement in the general health of the bird, as the latter is reflected in its positive effect on the aforementioned traits.…”
Section: Discussionmentioning
confidence: 99%
“…Cordia spp. and several plant extracts and their isolated compounds showed successful anti-inflammatory activity (Dixit and Mittal, 2013[ 3 ]; Ranjbar et al, 2013[ 20 ]) and they can be useful as cancer prevention or drug either (Parisotto et al, 2012[ 18 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to new drugs, herbal medicines and their relative compounds are frequently used to treat different inflammatory conditions, such as lung and skin inflammations as well as chronic diseases (Dixit and Mittal, 2013[ 3 ]; Garg et al, 2012[ 6 ]). Recently, we done an in-vitro study on anti-inflammatory properties of Cordia myxa fruit and results showed that the hydro-alcoholic extract was considerably effective in treatment of acute inflammation in rat (Ranjbar et al, 2013[ 20 ]). Cordia species plants are increasingly being referred to as a rich source of anti-inflamatory compounds (Ficarra et al, 1995[ 4 ]; Dixit and Mittal, 2013[ 3 ]).…”
Section: Introductionmentioning
confidence: 99%